EFFECTS OF WATERSHED LAND USE ON NITROGEN CONCENTRATIONS AND δ15 NITROGEN IN GROUNDWATER - Cole M.L.; Kroeger K.D.; Mcclelland J.W.; Valiela I. (My University, 2006)
Eutrophication is a major agent of change affecting freshwater, estuarine, and marine systems. It is largely driven by transportation of nitrogen from natural and anthropogenic sources. Research is needed to quantify this nitrogen delivery and to link the delivery to specific land-derived sources. In this study we measured nitrogen concentrations and δ15N values in seepage water entering three freshwater ponds and six estuaries on Cape Cod, Massachusetts and assessed how they varied with different types of land use. Nitrate concentrations and δ15N values in groundwater reflected land use in developed and pristine watersheds. In particular, watersheds with larger populations delivered larger nitrate loads with higher δ15N values to receiving waters. The enriched δ15N values confirmed nitrogen loading model results identifying wastewater contributions from septic tanks as the major N source. Furthermore, it was apparent that N coastal sources had a relatively larger impact on the N loads and isotopic signatures than did inland N sources further upstream in the watersheds. This finding suggests that management priorities could focus on coastal sources as a first course of action. This would require management constraints on a much smaller population.
Keywords: CAPE COD; GROUNDWATER; LAND USE; NITROGEN; STABLE ISOTOPES